All‐Aqueous Synthesis of Silica‐Encapsulated Quantum Dots with Functional Shells. Issue 44 (28th September 2017) - Feng, Huanhuan; ten Hove, Jan Bart; Zheng, Tingting; Velders, Aldrik H.; Sprakel, Joris
Abstract : We present a simple yet versatile method for encapsulating water‐dispersed quantum dots (QDs) in a silica shell. As our approach, does not require ligand exchange, the colloidal stability of the quantum dots is maintained throughout the process, which results in monodisperse core‐shell particles of individual quantum dots with a well‐defined silica shell whose thickness can be accurately controlled. While other methods often result in a reduction of luminescence, our approach can retain all or even increases the quantum efficiency of the semiconductor dots. We also show how amine‐functional groups can be expressed at the surface of the silica shell, while retaining QD photoluminescence properties, allowing further surface functionalization. Finally, we demonstrate the versatility of this strategy by including dopants into the silica shells to tailor the spectral response of the core‐shell particles by energy transfer. Abstract : A simple and all‐aqueous method is presented to prepare core‐shell quantum dots, encapsulated in a silica shell of tunable thickness, which can be functionalized with reactive groups and doped with energy transfer acceptors.